ANALYSIS OF FACTORS AFFECTING SHOPHOUSE VALUE IN LUBUK PAKAM CITY, DELI SERDANG REGENCY - Putri Harfitalia; Sugiharto Pujangkoro; Hilma Tamiami Fachrudin (Bajang Institute, 2023)
The purpose of this research is to analyze factors affecting shophouse value in Lubuk Pakam City, Deli Serdang Regency. This type of research in this study uses quantitative research. Population in this study are shop owners or tenants in Lubuk Pakam City, totaling 268 shophouses. Method of determining the sample using purposive sampling. From the calculation, it is found that as many as 73 shophouses would be used as samples and then broken down into 3 sections according to the urban village in Lubuk Pakam City. The analysis in this study used descriptive statistical and partial (t) test. The results show that physical factor has a significant effect on shophouse value in Lubuk Pakam City, Deli Serdang Regency. Accessibility factor has a significant effect on shophouse value in Lubuk Pakam City, Deli Serdang Regency. Environmental factor has a significant effect on shophouse value in Lubuk Pakam City, Deli Serdang Regency. Facility factor has a significant effect on shophouse value in Lubuk Pakam City, Deli Serdang Regency.